g*bp-Continuous Multifunction - Khalaf, Alias B.; Dawod, Suzan N. (International Journal of Advanced Mathematical Sciences, 2013)
In this paper we introduce a new class of multifunction called Upper(lower) g*bp-continuous multifunction, Up-per(lower) almost g*bp-continuous multifunction, Upper(lower) weakly g*bp-continuous multifunction and Up-per(lower) contrag*bp-continuous multifunction in topological spaces,and study some of their basic properties andrelations among them.